Contribution of non-HLA incompatibility between donor and recipient to kidney allograft survival: genome-wide analysis in a prospective cohort. Issue 10174 (2nd March 2019) - Reindl-Schwaighofer, Roman; Heinzel, Andreas; Kainz, Alexander; van Setten, Jessica; Jelencsics, Kira; Hu, Karin; Loza, Bao-Li; Kammer, Michael; Heinze, Georg; Hruba, Petra; Koňaříková, Alena; Viklicky, Ondrej; et al.
Summary: Background: The introduction of HLA matching of donors and recipients was a breakthrough in kidney transplantation. However, half of all transplanted kidneys still fail within 15 years after transplantation. Epidemiological data suggest a fundamental role of non-HLA alloimmunity. Methods: We genotyped 477 pairs of deceased donors and first kidney transplant recipients with stable graft function at three months that were transplanted between Dec 1, 2005, and April 30, 2015. Genome-wide genetic mismatches in non-synonymous single nucleotide polymorphisms (nsSNPs) were calculated to identify incompatibilities in transmembrane and secreted proteins. We estimated the association between nsSNP mismatch and graft loss in a Cox proportional hazard model, adjusting for HLA mismatch and clinical covariates. Customised peptide arrays were generated to screen for antibodies against genotype-derived mismatched epitopes in 25 patients with biopsy-confirmed chronic antibody-mediated rejection. Findings: 59 268 nsSNPs affecting a transmembrane or secreted protein were analysed. The median number of nsSNP mismatches in immune-accessible transmembrane and secreted proteins between donors and recipients was 1892 (IQR 1850–1936). The degree of nsSNP mismatch was independently associated with graft loss in a multivariable model adjusted for HLA eplet mismatch ( HLA-A, HLA-B, HLA-C, HLA-DP, HLA-DQ, and HLA-DR ). Each increase by a unit of one IQR had an HR of 1·68 (95% CI 1·17–2·41, p=0·005). 5-year death censored graft survival was 98% in the quartile with the lowest mismatch, 91% in the second quartile, 89% in the third quartile, and 82% in the highest quartile (p=0·003, log-rank test). Customised peptide arrays verified a donor-specific alloimmune response to genetically predicted mismatched epitopes. Interpretation: Genetic mismatch of non-HLA haplotypes coding for transmembrane or secreted proteins is associated with an increased risk of functional graft loss independently of HLA incompatibility. As in HLA alloimmunity, donor-specific alloantibodies can be identified against genotype derived non-HLA epitopes. Funding: Austrian Science Fund, WWTF (Vienna Science and Technology Fund), and Ministry of Health of the Czech Republic.